INFLUENCE OF ELICITORS OF VARIOUS NATURES ON THE ACTIVITY OF ENZYMES INVOLVED IN BIOSYNTHESIS OF LIGNANS IN CALLUS CULTURES LINUMA USTRIACUM L. (Proceedings of the YSU B: Chemical and Biological Sciences, 2033)
Summary The effect of mannan, β-1,3 glucan and ancymidol on the activity of enzymes involved in biosynthesis of lignans, podophyllotoxin, 5-metoxypodophyllotoxin and their derivatives production in the callus culture of Linum  austriacum was investigated. The activities of L-Phenylalanine ammonia-lyase, Polyphenoloxidase, Tyrosinase, soluble Phenolase, wall-bound and soluble Oxidases were determined. Effects of elicitation on different steps of metabolic pathways in L. austriacum callus cultures were revealed.  It was concluded that elicitors, which could stimulate the biosynthetic pathways affecting on activity of key enzymes, could stimulate the production of podophyllotoxins.
Keywords: podophyllotoxin; 5-metoxypodophyllotoxin; ancymidol; β-1,3 glucan; enzymes